Cinéma/Science-fiction : vers un changement de paradigme critique ? - Simon Bréan (ReS Futurae)
Science fiction is currently integrated into the « mainstream » cinema, a very broad category that allows for the creation of major projects, whose objective of spectacular entertainment is no longer incompatible with a certain intellectual ambition and whose potential for social or even philosophical criticism is put forward as a commercial argument. The repercussions – and the manifestations – of this cultural validation are countless. We will question here the critical paradigm shift that would be the most relevant to take these evolutions into account. First of all, it seems essential to take into account the change of scale, correlated to the change of status, of science fiction cinema, since the 1980s. It would thus be necessary to measure the impact of the globalized diffusion of cinematographic productions on the conception of the works, by questioning in particular the articulation of the megatext of science fiction to its various national macrotexts. Secondly, this increased circulation of science fiction images in cinema favors the construction of an interpretive competence of the spectators, and thus makes it possible to create more sophisticated narrative and visual strategies, including in works intended for the general public. Finally, this singularization of science fiction cinema is part of an increasingly complex transmedia continuum, which is historically marked by the classic interactions between literature and cinema, but which does no longer limit itself to these. To take into account the dynamics of science fiction, its processes of concretization of visual novums and of setting in narrative of strangeness yet so familiar, is to give oneself the possibility of exploring certain specificities of the cinematographic art, but it is also to identify what this cinema brings, in its own right, to a science fiction less transcendent than it seems, and which takes strength from each incarnation.